Thermography in a Distribution Operator, Common Real Problems - , Jacob G. Fantidis (Archives of Current Research International, 2018)
Infrared thermography offers to the distribution operators the possibility to monitor their critical equipment. Early knowing the faulty or defective equipment the operators have the ability to evaluate the faults. With this knowledge, electric power distribution companies can avoid failures on their networks. In the vital areas which are installed at the High Voltage to Medium Voltage substations the interest is focusing on the equipment which is not checked by their SCADA system. In this article, the Central Greece Regional Department of the Greek distribution network operator (HEDNO S.A.) presents the most frequently reported problems during its thermographic investigations. Recommendations and interpretations, based on the experience and the database of the Central Greece department of HEDNO, are given as well.